The Drought and Food Crisis in the Horn of Africa : Impacts and Proposed Policy Responses for Kenya - Demombynes, Gabriel; Kiringai, Jane (World Bank, Washington, DC, 2012)
As the world begins to feel the effects of climate change, the frequency of droughts is increasing in the Horn of Africa. In Kenya, the drought and food crisis affect welfare through two main channels. The first channel is the increased mortality of livestock in drought-affected areas, which are home to 10 percent of the country's population. The second channel is by exacerbating increases in food prices, which are largely driven by worldwide price trends. Considering these two channels, this note identifies four broad policy changes that can reduce Kenya's future vulnerability to such shocks: (i) investment in people in the arid and semiarid lands; (ii) reform of Kenya's maize policy; (iii) review of the East African Community grain trade policy; and (iv) formulation of a unified social protection system.